HIV-Positive Status Disclosure and Associated Factors among HIV-Positive Adult Patients Attending Art Clinics at Public Health Facilities of Butajira Town, Southern Ethiopia - Tamirat Melis Berhe; Lire Lemma; Addissu Alemayehu; Desalegn Ajema; Mustefa Glagn; Samuel Dessu (AIDS Research and Treatment)
Background. Human immunodeficiency virus-positive status disclosure is the process of informing one’s HIV-positive status to others. It is the base for accessing care and treatment programs, attaining psychosocial support, reducing stigma, adhering to treatment, and promoting safer health. Even though different strategies were done in Ethiopia to increase the magnitude of HIV status disclosure among HIV-positive patients, the magnitude is still low. The magnitude of HIV-positive status disclosure was not assessed yet after initiation of the new strategy (test and treat strategy). The aim of this study is to assess the magnitude and factors associated with HIV-positive status disclosure among HIV-positive adults attending antiretroviral therapy clinic at the public health facilities of Butajira town. Methods. Institution-based cross-sectional study was conducted at public health facilities of Butajira town. A total of 414 study participants were selected by systematic random sampling technique. Data were collected by using pretested interviewer-administered semistructured questionnaire. The collected data were entered into EpiData3.1 and exported to SPSS version 23. Bivariate and multivariable logistic regression analysis was used to identify factors associated with HIV-positive status disclosure. The strength of association was assessed by crude odds ratio and adjusted odds ratio for bivariate and multivariable logistic regression analysis, respectively. Statistically significance was declared at p value <0.05 and 95% CI. Results. The magnitude of HIV-positive status disclosure was 90%. Discussing about safer sex (AOR: 3.5; 95% CI: 1.3, 9.4), viral load suppression (AOR: 4; 95% CI: 1.5, 10.1), having good ART adherence (AOR: 6; 95% CI: 2.4, 14.0), receiving counseling (AOR: 2.5; 95% CI: 1.01, 6.3), and perceiving stigma (AOR: 0.25; 95% CI: 0.09, 0.60) were the independent factors associated with HIV-positive status disclosure. Conclusion. Although the majority of the participants (90%) of them disclosed their HIV-positive status, lack of disclosure by few people can tackle HIV prevention and control programs. Health programs could improve disclosure of HIV-positive status by providing counseling service, strengthening adherence of antiretroviral therapy, suppressing viral load, and avoiding (reducing) stigma on HIV-positive patients by their community.